Fractures of the distal clavicle: comparison between two surgical treatment methods - José Carlos Souza Vilela (Revista Brasileira de Ortopedia, 2015)
OBJECTIVE: To compare the clinical and radiographic results from osteosynthesis of fractures of the lateral third of the clavicle, using two methods: T plates or anchors together with Kirschner wires.METHODS: Fifteen patients of mean age 34.3 years (range: 19-57) and mean follow-up 22.7 months (range: 14-32) were evaluated. In nine cases, a T plate was used; and in six cases, coracoclavicular fixation was used with anchors in the coracoid process and Kirschner wires through the acromioclavicular joint. The evaluation included the Constant score, personal satisfaction and radiographic assessment.RESULTS: Both types of treatment achieved consolidation in all cases. Group 1 presented a higher Constant score (83.4) than that of Group 2 (76.4) (p = 0.029). Neither of the techniques presented any severe complications, and mild complications were only observed in Group 2 (80%), mostly consisting of migration of the Kirschner wire and superficial infection.CONCLUSION: Surgical treatment of fractures of the distal clavicle using T plates provided the same consolidation rate as shown by coracoclavicular fixation with anchors in the coracoid process and Kirschner wires through the acromioclavicular joint, and better clinical results.LEVEL OF EVIDENCE: Level III evidence was obtained. Comparative retrospective study and therapeutic study were performed.